Penerapan Model Pembelajaran Kooperatif Tipe Make A Match Untuk Meningkatkan Hasil Belajar - Heri Kurnia; Gilang Septera (Academy of Education Journal, 2019)
This research is motivated by learning at SMA Negeri 1 Cikatomas, Kabepaten Tasikmalaya, that the learning techniques used are still less attractive to students, so students' motivation and learning achievement for learning is relatively low. In view of this, it is better to deliver lessons with an interesting learning model that is expected, because learning activities in children depend on the way the teacher presents the lesson. Therefore, researchers use the cooperative model of make a match type of learning in improving student Civics learning outcomes.This research is a classroom action research (CAR). In the CAR research stage consists of four stages, namely planning, implementing actions, observing and reflecting. The results showed that the application of the make a match type of cooperative learning model could improve student Civics learning outcomes. This is indicated by the level of mastery learning also increased from the initial test of 45%, in the first cycle to 56% and in the second cycle rose to 82%.The conclusion of this research is the application of the make a match type of cooperative learning model can improve the learning outcomes of PKn class XI IPS 3 students of SMA Negeri 1 Cikatomas with 29 students.